2022
DOI: 10.31083/j.jin2101028
|View full text |Cite
|
Sign up to set email alerts
|

Digital dementia in the internet generation: excessive screen time during brain development will increase the risk of Alzheimer's disease and related dementias in adulthood

Abstract: Converging evidence from biopsychosocial research in humans and animals demonstrates that chronic sensory stimulation (via excessive screen exposure) a fects brain development increasing the risk of cognitive, emotional, and behavioural disorders in adolescents and young adults. Emerging evidence suggests that some of these effects are similar to those seen in adults with symptoms of mild cognitive impairment (MCI) in the early stages of dementia, including impaired concentration, orientation, acquisition of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 110 publications
0
13
0
5
Order By: Relevance
“…Since these studies did not specifically examine the link between internet use and MCI, we could say that we were the first to find that internet use might help reduce the risk of MCI. But we have to point out, studies have shown that heavy use of electronic devices (i.e., more than 2–3 h/day exposure to electronic media including computers, television, and mobile devices such as tablets, smartphones, and laptops) cloud also increase the risk of cognitive impairment ( 23 ). Therefore, we recommend that the elderly should not spend more than 2 h on the computer on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
“…Since these studies did not specifically examine the link between internet use and MCI, we could say that we were the first to find that internet use might help reduce the risk of MCI. But we have to point out, studies have shown that heavy use of electronic devices (i.e., more than 2–3 h/day exposure to electronic media including computers, television, and mobile devices such as tablets, smartphones, and laptops) cloud also increase the risk of cognitive impairment ( 23 ). Therefore, we recommend that the elderly should not spend more than 2 h on the computer on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
“…Ihre Begründung in aller Kürze: „Die CDC-Schätzungen beruhen ausschließlich auf Faktoren in Bezug auf Alter, Geschlecht, Rasse und ethnische Zugehörigkeit von Personen, die vor 1950 geboren sind und die in kritischen Phasen der Gehirnentwicklung keinen Zugang zu mobiler digitaler Technologie hatten. Im Gegensatz zu früheren Generationen verbringt der durchschnittliche 17- bis 19-Jährige etwa 6 Stunden pro Tag mit mobilen digitalen Geräten (Smartphones, Tablets und Laptops) während Personen, die vor 1950 geboren wurden, im gleichen Alter null Stunden damit verbrachten“ 30 . Und dann fassen die Autoren zusammen, was man über die negativen Auswirkungen digitaler Informationstechnik auf Gehirnentwicklung und Bildung weiß.…”
Section: Geringere Bildung In Jungen Jahren Erhöht Die Wahrscheinlich...unclassified
“…noch kommen werden. liche 17-bis 19-Jährige etwa 6 Stunden pro Tag mit mobilen digitalen Geräten (Smartphones, Tablets und Laptops) während Personen, die vor 1950 geboren wurden, im gleichen Alter null Stunden damit verbrachten"[30]. Und dann fassen die Autoren zusammen, was man über die negativen Auswirkungen digitaler Informationstechnik auf Gehirnentwicklung und Bildung weiß.Aus meiner Sicht geht es hierbei letztlich um Folgerungen aus der wichtigsten Erkenntnis im Bereich der Neurowissenschaften im letzten halben Jahrhundert, der Neuroplastizität.…”
unclassified
“…However, the effect of interactive real visual cues on balance training performance remains unknown. Further, screen-based technology has potential health consequences with excessive use including links to digital fatigue, attention deficits, and neurodegeneration [38]- [40], and may also affect memory recall [41]. Therefore, alternative feedback mechanisms for at-home therapy that do not rely on a screen are needed.…”
Section: Introductionmentioning
confidence: 99%